2010
DOI: 10.1523/jneurosci.5540-09.2010
|View full text |Cite
|
Sign up to set email alerts
|

Sequentially Switching Cell Assemblies in Random Inhibitory Networks of Spiking Neurons in the Striatum

Abstract: The striatum is composed of GABAergic medium spiny neurons with inhibitory collaterals forming a sparse random asymmetric network and receiving an excitatory glutamatergic cortical projection. Because the inhibitory collaterals are sparse and weak, their role in striatal network dynamics is puzzling. However, here we show by simulation of a striatal inhibitory network model composed of spiking neurons that cells form assemblies that fire in sequential coherent episodes and display complex identity-temporal spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
143
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(161 citation statements)
references
References 102 publications
18
143
0
Order By: Relevance
“…The activity of striatal MSNs and their response to excitatory input, is further modulated by concurrent inhibition derived from collaterals of neighboring MSNs and local interneurons (Tepper and Plenz, 2006;Ponzi and Wickens, 2010). As a first test of the hypothesis that histamine modulates inhibitory input to MSNs we used intrastriatal electrical stimulation, in the presence of blockers of excitatory transmission, to recruit all inhibitory afferents to MSNs simultaneously.…”
Section: Histamine Differentially Modulates Striatal Inhibitionmentioning
confidence: 99%
“…The activity of striatal MSNs and their response to excitatory input, is further modulated by concurrent inhibition derived from collaterals of neighboring MSNs and local interneurons (Tepper and Plenz, 2006;Ponzi and Wickens, 2010). As a first test of the hypothesis that histamine modulates inhibitory input to MSNs we used intrastriatal electrical stimulation, in the presence of blockers of excitatory transmission, to recruit all inhibitory afferents to MSNs simultaneously.…”
Section: Histamine Differentially Modulates Striatal Inhibitionmentioning
confidence: 99%
“…However, physiological studies have found these lateral connec- tions to be sparse, weak, and asymmetrical (Jaeger et al, 1994;Tunstall et al, 2002;Koos et al, 2004;Tepper et al, 2004;Planert et al, 2010) thus casting doubt on competitive inhibition as a key computational process in the information processing of the striatum. Ponzi and Wickens (2010) recently showed that in a model based on a realistic striatal inhibitory network, cells form assemblies that fire in sequential coherent episodes. Cell members of the same assembly showed correlated firing rate fluctuations at behaviorally relevant timescales, whereas cell members in different assemblies were negatively correlated.…”
Section: Formation Of Dynamically Changing Functional Correlations Wimentioning
confidence: 99%
“…It is believed that the striatum integrates these convergent streams of information, with the resulting activity acting on basal ganglia output nuclei connected to association and motor control areas in the cortex (Alexander et al 1986). Computational and experimental studies suggest that the converging input to the striatum leads to the formation of functionally specialized subsets of MSNs with temporally correlated activity patterns (Adler et al 2012;Carrillo-Reid et al 2008;Humphries et al 2009;Ponzi and Wickens 2010;Yim et al 2011). These findings in the striatum, and a large body of work focusing on cortical circuits (Averbeck et al 2006;Bair et al 2001;Cohen and Maunsell 2009;Mitchell et al 2009;Shadlen and Newsome 1998;Zohary et al 1994), implicate correlated activity in neural computation and behavior.…”
mentioning
confidence: 99%